PERAN FAKTOR SITUASIONAL TERHADAP KEPUTUSAN PEMBELIAN IMPULSIF (STUDI KASUS TOKO BASMALAH DI PAKUSARI) - Devi Lestari; Maheni Ika Sari; Ahmad Hasan Hafidzi (Relawan Jurnal Indonesia, 2020)
The purpose of this study was to determine and analyze: 1) the effect of the role of Store Environment on implusive purchases. 2) the effect of the role of Time Pressure on implusive purchases. 3) the influence of the role of Preceived Crowding on implusive purchases. This research design is explanatory (explanatory research) with a quantitative approach. This research was conducted at the Basmalah Pakusari Store in Jember. The population in this study were all consumers in the Basmalah Pakusari store. The number of samples amounted to 140 with a purposive sampling technique. Data were collected by questionnaire and analyzed by multiple linear regression. The results of hypothesis testing conclude that: 1) Store Environment influences implusive purchases. 2) Time Preassure affects the implusive purchase. 3) Perceived Crowding influences implusive purchases. Thus the hypothesis in this study was accepted and statistically proven. It is understood that every increase in the independent variable will be followed by an increase in the dependent variable and vice versa.